Assessing the Diversity and Specificity of Two Freshwater Viral Communities through Metagenomics - Roux, Simon; Enault, Francois; Robin, Agnès; Ravet, Viviane; Personnic, Sébastien; Theil, Sébastien; Colombet, Jonathan; Sime-Ngando, Télesphore; Debroas, Didier (PloS one, 2012)
Transitions between saline and fresh waters have been shown to be infrequent for microorganisms. Based on host-specific interactions, the presence of specific clades among hosts suggests the existence of freshwater-specific viral clades. Yet, little is known about the composition and diversity of the temperate freshwater viral communities, and even if freshwater lakes and marine waters harbor distinct clades for particular viral sub-families, this distinction remains to be demonstrated on a community scale.To help identify the characteristics and potential specificities of freshwater viral communities, such communities from two lakes differing by their ecological parameters were studied through metagenomics. Both the cluster richness and the species richness of the Lake Bourget virome were significantly higher that those of the Lake Pavin, highlighting a trend similar to the one observed for microorganisms (i.e. the specie richness observed in mesotrophic lakes is greater than the one observed in oligotrophic lakes). Using 29 previously published viromes, the cluster richness was shown to vary between different environment types and appeared significantly higher in marine ecosystems than in other biomes. Furthermore, significant genetic similarity between viral communities of related environments was highlighted as freshwater, marine and hypersaline environments were separated from each other despite the vast geographical distances between sample locations within each of these biomes. An automated phylogeny procedure was then applied to marker genes of the major families of single-stranded (Microviridae, Circoviridae, Nanoviridae) and double-stranded (Caudovirales) DNA viruses. These phylogenetic analyses all spotlighted a very broad diversity and previously unknown clades undetectable by PCR analysis, clades that gathered sequences from the two lakes. Thus, the two freshwater viromes appear closely related, despite the significant ecological differences between the two lakes. Furthermore, freshwater viral communities appear genetically distinct from other aquatic ecosystems, demonstrating the specificity of freshwater viruses at a community scale for the first time.